Sesbania grandiflora Extract Reduces ALP and GGT in Paracetamol Toxicity: Ekstrak Sesbania grandiflora Mengurangi ALP dan GGT pada Toksisitas Parasetamol - Veronika Oktaruliawan; Jamilatur Rohmah (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Oxidative stress generated by excessive free radicals contributes to hepatic injury, particularly during metabolism of hepatotoxic drugs. Specific Background: Paracetamol overdose produces the reactive metabolite N-acetyl-p-benzoquinone imine, which triggers lipid peroxidation and elevates liver enzymes such as Alkaline Phosphatase (ALP) and γ-Glutamyl Transferase (GGT). Sesbania grandiflora leaves contain bioactive compounds including flavonoids, alkaloids, and tannins with antioxidant properties. Knowledge Gap: Scientific evidence describing the biochemical response of ALP and GGT to Sesbania grandiflora leaf extract under paracetamol-induced hepatotoxic conditions remains limited. Aims: This study evaluated the biochemical changes in ALP and GGT levels and oxidative stress marker malondialdehyde (MDA) in male Wistar rats administered toxic paracetamol doses followed by graded Sesbania grandiflora leaf extract treatment. Results: Experimental randomized controlled laboratory research involving 28 rats demonstrated significant differences in MDA, ALP, and GGT values across treatment groups (p<0.05). Paracetamol administration elevated oxidative stress and liver enzyme parameters, while extract administration decreased MDA and reduced ALP and GGT levels. The 1000 mg/kg body weight dose produced enzyme values approaching physiological ranges. Novelty: This study presents combined biochemical evaluation of oxidative stress indicators and dual liver enzyme parameters following graded Sesbania grandiflora leaf extract administration in paracetamol-induced hepatic injury. Implications: Sesbania grandiflora leaf extract represents a potential natural hepatoprotective candidate with antioxidant activity relevant for managing drug-induced liver injury and supporting development of plant-based therapeutic agents. Highlights: Highest Administered Dose Returned Enzyme Biomarkers Close to Physiological Values. Antioxidant Administration Lowered Lipid Peroxidation Indicator Concentrations in Treated Animals. Statistical Analysis Confirmed Significant Biochemical Differences Between Intervention and Control Groups. Keywords: Sesbania Grandiflora; Hepatoprotection; Oxidative Stress; Alp; Gamma Glutamyl Transferase